A Rho GTPase signaling pathway is used reiteratively in epithelial folding and potentially selects the outcome of Rho activation. - Nikolaidou, K.K.; Barrett, K. (Current Biology, 2004)
A single Rho GTPase family member is capable of initiating several different processes, including cell cycle regulation, cytokinesis, cell migration, and transcriptional regulation . It is not clear, however, how the Rho protein selects which of these processes to initiate. Guanine nucleotide exchange factors (GEFs), proteins that activate Rho GTPases, could be important in making this selection. We show here that in vivo, DRhoGEF2, a GEF that is ubiquitously expressed and specific for Rho1, is reiteratively required for epithelial folding and invagination, but not for other processes regulated by Rho. The limitation of DRhoGEF2 function supports the hypothesis that the GEF selects the outcome of Rho activation. DRhoGEF2 exerts its effects in gastrulation through the regulation of Myosin II to orchestrate coordinated apical cell constriction. Apical myosin localization is also regulated by Concertina (Cta), a Galpha(12/13) family member that is thought to activate DRhoGEF2 and is itself activated by a putative ligand, Folded gastrulation (Fog). Fog and Cta also play a role in the morphogenetic events requiring DRhoGEF2, suggesting the existence of a conserved signaling pathway in which Fog, Cta, and DRhoGEF2 locally activate Myosin for epithelial invagination and folding.